Prevalence of Undiagnosed Depression in Patients With Type 2 Diabetes - Alajmani, Dina Siddiq Abdulhadi; Alkaabi, Amna Mohamad; Alhosani, Mariam Waleed; Folad, Ayesha Abdulaziz; Abdouli, Fawzia Ahmed; Carrick, Frederick Robert; Abdulrahman, Mahera (Frontiers in Endocrinology, 2019)
Introduction: Type 2 Diabetes Mellitus (T2DM) is the most prevalent type of diabetes among adults and constitutes around 90% of all cases. Substantial evidence demonstrates that depression in the context of diabetes is associated with a wide range of adverse consequences. Methods: This study was conducted to assess the depression among T2DM patients attending diabetic clinics, Dubai Health Authority (DHA). Depressive symptoms were assessed by using both Arabic and English version of the Beck Depression Inventory. Results: Out of 1050 diabetic patients approached, 559 were within our inclusion criteria and agreed to participate in this study (Response rate of 53%). The overall depression prevalence using a cutoff of 16 was 17%. When we assessed the level of depression amongst participants in association with their sociodemographic and clinical characteristics, there was a significant difference between age groups (p<0.00001); gender (p<0.0001); nationality (p<0.00001); educational level (p<0.00001); and employment status (p<0.0001). The type of clinic in which the T2DM patients were attending (e.g., diabetes mini-clinic versus General Family Clinic) was also significantly associated with depression (p< 0.0001). Conclusion: Our results demonstrate that the intensive service being given in a diabetes mini-clinic compared to routine PHC clinics appears to benefit the psychological aspects of T2DM patients in the UAE population resulting in a lower incidence of depression than commonly seen in a diabetic population. We have identified a need for the establishment of these mini-clinics in each PHC clinics.